PEREMPUAN DAN KETAHANAN EKONOMI KELUARGA (STUDI DI KAMPUNG KUE RUNGKUT SURABAYA) - Alie, Azizah; Elanda, Yelly (Journal of Urban Sociology, 2019)
Economic resilience is one component of strengthening family resilience. In the cake village, almost all of her women work in the culinary field of making and selling cakes. This cake village was created originating from the number of women factory workers who were laid off. The majority of them are nomads from several areas in East Java. Instead of returning home due to termination of employment, these women then make a business in the culinary field. From the results of the experiment several times it turned out that the cake became a profitable commodity. At first, the home industry had stumbled and encountered obstacles, but now the cake entrepreneurs have managed to reap the rewards and even the cake has become a mainstay product. This study aims to describe how the role of women in building family economic resilience in the cake village. This study uses a qualitative method by interviewing women who are entrepreneurs of cakes in the village of Rungkut, Surabaya. The results of this study indicate that the role of women in building family economic resilience does not only affect the small families they foster, but it has a broad effect on the economic resilience of families in the cake village. The role of these women is as the backbone of the family, as partners of the husband, as agents of change and other women empowerers. Women are able to be involved and play a role in family economic security due to gender equality in the family.Â Keywords: Family Economic Resilience, Kampung Kue, Role of Women, Gender Equality.